PALESTINE HIJACKED : HOW ZIONISM FORGED AN APARTHEID STATE FROM RIVER TO SEA - Suarez, Thomas (Crescent News (K.L) Sdn. Bhd., 2024)
The Israel-Palestine “conflict” is typically understood to be a clash between two ethnic groups—Arabs and Jews—inhabiting the same land. Thomas Suárez digs deep below these preconceptions and their supporting “narratives” to expose something starkly different: The violent take-over of Palestine by a European racial-nationalist settler movement, Zionism, using terror to assert by force a claim to the land that has no legal or moral basis. Drawing extensively from original source documents, many revealed here for the first time, Suárez interweaves secret intelligence reports, newly-declassified military and diplomatic correspondence, and the terrorists’ own records boasting of their successes. His shocking account details a litany of Zionist terrorism against anyone in their way—the indigenous Palestinians, the British who had helped establish Zionism, and Jews who opposed the Zionist agenda. Far from being isolated atrocities by rogue groups, the use of terror was deliberate and sustained, carried out or supported by the same leaders who then established and led the Israeli state. We are still living this history: The book proves that Israel's regime of Apartheid against the Palestinians and the continued expropriation of their country are not the result of complex historical circumstances, but the intended, singular goal of Zionism since its beginning.